1993
DOI: 10.1002/humu.1380020505
|View full text |Cite
|
Sign up to set email alerts
|

Genomic instability occurs in colorectal carcinomas but not in adenomas

Abstract: Genomic instability, as demonstrated by the presence of additional alleles at short tandemly repeated (STR) loci, has recently been observed in colorectal tumours from individuals with hereditary nonpolyposis colorectal cancer (HNPCC), and in some sporadic tumours. These neoplasms have been called replication error positive (RER+). In this study, we confirm the presence of genomic instability in a proportion of unselected colorectal carcinomas but find no evidence of instability in adenomas. We further report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 17 publications
5
52
0
Order By: Relevance
“…The commonly lost region is indicated by a bar above markers. Numbers on a thin line below the bars indicate lymphomas retaining both alleles in 251 informative lymphomas examined cancers and neuroblastomas (Suzuki et al, 1989;Young et al, 1993;Chang et al, 1995;Bandera, 1997). Therefore, a human homolog of the candidate tumor suppressor gene in Tlsr4 may be involved in the development of some of those human tumors, although the types of mouse and human tumors are di erent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly lost region is indicated by a bar above markers. Numbers on a thin line below the bars indicate lymphomas retaining both alleles in 251 informative lymphomas examined cancers and neuroblastomas (Suzuki et al, 1989;Young et al, 1993;Chang et al, 1995;Bandera, 1997). Therefore, a human homolog of the candidate tumor suppressor gene in Tlsr4 may be involved in the development of some of those human tumors, although the types of mouse and human tumors are di erent.…”
Section: Discussionmentioning
confidence: 99%
“…The D12Mit279 locus in the vicinity of Tlsr4 showed allelic loss at a frequency of as high as 62% and the frequency was not a ected by the presence or absence of a p53-de®cient allele in irradiated mice (Matsumoto et al, 1998). Interestingly, the Tlsr4 interval on mouse chromosome 12 is homologous to human chromosome 14q32 ± 33 where frequent allelic losses have been found in a variety of tumors: ovarian tumors (Bandera, 1997), colorectal carcinomas (Young et al, 1993), neuroblastomas (Suzuki et al, 1989) and invasive bladder cancer (Chang et al, 1995). Therefore, analysis of Tlsr4 may lead to isolation of a candidate of the tumor suppressor gene not only in Tlsr4 but also in the human 14q32-33 region.…”
Section: Introductionmentioning
confidence: 99%
“…DNA mis-match repair defects have been found to occur in approximately 17% of sporadic (nonhereditary) cancers (Aaltonen et al, 1994;Ionov et al, 1993;Lothe et al, 1993;Young et al, 1993;Kim et al, 1994;Thibodeau et al, 1993) and up to 86% of tumours from hereditary non-polyposis colorectal cancer (HNPCC) patients (Aaltonen et al, 1993, …”
Section: Discussionmentioning
confidence: 99%
“…Approximately 17% of sporadic colon tumours and up to 85% of tumours from hereditary non-polyposis colorectal cancer (HNPCC) patients show evidence of microsatellite instability (MSI) which arises from defects in the DNA mismatch repair mechanisms (Aaltonen et al, , 1994Lothe et al, 1993;Young et al, 1993;Wu et al, 1994;Kim et al, 1994). Recent studies suggest that one common type of mutation, occuring in tumours and tumour cell lines with mismatch repair defects, is a reduction in the length of mononucleotide tracts (Ionov et al, 1993;Markowitz et al, 1995;Chen et al, 1995;Bubb et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Scattered reports have suggested that individuals bearing the`short' (S) allele either have an increased incidence of certain tumors and/or that such tumors manifest a more aggressive behavior. The associated neoplasms include soft-tissue sarcomas (Kato et al, 1990), oral cancers (Saranath et al, 1990), colorectal cancers (Young et al, 1994), nonHodgkin's lymphoma (Crossen et al, 1994), breast cancer (Champeme et al, 1992), and non-SCLC lung cancer (Kawashima et al, 1988). In contrast, at least one report has suggested that the`SS' genotype protects against hepatocellular cancer (Taylor et al, 1993).…”
Section: Small Cell Lung Cancer (Sclc)mentioning
confidence: 99%